The island model as a Markov dynamic system - Schaefer, Robert; Byrski, Aleksander; Smołka, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
Parallel multi-deme genetic algorithms are especially advantageous because they allow reducing the time of computations and can perform a much broader search than single-population ones. However, their formal analysis does not seem to have been studied exhaustively enough. In this paper we propose a mathematical framework describing a wide class of island-like strategies as a stationary Markov chain.
Keywords: genetic algorithms; asymptotic analysis; global optimization; parallel evolutionary algorithms; Markov chain modeling